Abstract algebra : a gentle introduction - Mullen, Gary L; Sellers, James A (Boca Raton: CRC Press, 2017)
This book advantages a trend in mathematics textbook publishing towards smaller, less expensive and brief introductions to primary courses. The authors move away from the 'everything for everyone' approach so common in textbooks. Instead, they provide the reader with coverage of numerous algebraic topics to cover the most important areas of abstract algebra.
Elementary Number Theory -- Groups -- Rings -- Fields -- Finite Fields -- Vector Spaces -- Polynomials -- Linear Codes -- Appendix -- Hints and Partial Solutions to Selected Exercises -- Bibliography -- Index
Includes bibliographical references and index.
Keywords: Algebra Abstract -- Textbooks; Groups; Rings; Fields